Synergistic inhibition of aggressive breast cancer cell migration and invasion by cytoplasmic delivery of anti-RhoC silencing RNA and presentation of EPPT1 peptide on "smart" particles - Kaushal, Neha; Tiruchinapally, Gopinath; Yüksel Durmaz, Yasemin; Bao, Liwei; Gilani, Rabia; Merajver, Sofia D.; ElSayed, Mohamed E. H. (Elsevier Science Bv, 2018)
Overexpression of RhoC protein in breast cancer patients has been linked to increased cancer cell invasion, migration, and metastases. Suppressing RhoC expression in aggressive breast cancer cells using silencing RNA (siRNA) molecules is a viable strategy to inhibit the metastatic spread of breast cancer. In this report, we describe the synthesis of a series of asymmetric pH-sensitive, membrane-destabilizing polymers engineered to complex anti-RhoC siRNA molecules forming "smart" nanoparticles. Using beta-CD as the particle core, polyethylene glycol (PEG) chains were conjugated to the primary face via non-cleavable bonds and amphiphilic polymers incorporating hydrophobic and cationic monomers were grafted to the secondary face via acid-labile linkages. We investigated the effect of PEG molecular weight (2 & 5 kDa) on transfection capacity and serum stability of the formed particles. We evaluated the efficacy of EPPT1 peptides presented on the free tips of the PEG brush to function as a targeting ligand against underglycosylated MUC1 (uMUC1) receptors overexpressed on the surface of metastatic breast cancer cells. Results show that "smart" nanoparticles successfully delivered anti-RhoC siRNA into the cytoplasm of aggressive SUM149 and MDA-MB-231 breast cancer cells, which resulted in a dose-dependent inhibition of cell migration and invasion. Further, EPPT1-targeted nanoparticles demonstrate a synergistic inhibition of cell migration and invasion imparted via RhoC knockdown and EPPT1-mediated signaling via the uMUC1 receptor.
WOS: 000448396000009
PubMed ID: 30149048
Keywords: PH-Sensitive Polymers; Smart Particles; RhoC Protein; EPPT1/uMUC1 Receptor Interaction; Breast Cancer Cell migration and Invasion